STRUCTURAL MECHANISM OF CO2+ OXIDATION BY THE PHYLLOMANGANATE BUSERITE - Manceau A.; Silvester E.; Bartoli C.; Lanson B.; Drits V.A. (My University, 1997)
The geochemistry of Co at the Earth's surface is closely associated with that of man- ganese oxides. This geochemical association results from the oxidation of highly soluble Co21 to weakly soluble Co31 species, coupled with the reduction of Mn41 or Mn31 ions, initially present in the manganese oxide sorbent, to soluble Mn 21. The structural mech- anism of this Co immobilization-manganese oxide dissolution reaction was investigated at the buserite surface. Co-sorbed samples were prepared at different surface coverages by equilibrating a Na-exchanged buserite suspension in the presence of aqueous Co21 at pH 4. The structure of Co-sorbed birnessite obtained by drying buserite samples was determined by X-ray diffraction (XRD) and powder and polarized EXAFS spectroscopy. For each sample we determined the proportion of interlayer cations and layer vacancy sites, the Co21/(Co21 1 Co31) ratio, the nature of Co sorption crystallographic sites, and the proportion of interlayer vs. layer Co. From this in-depth structural characterization two distinct oxidation mechanisms were identified that occur concurrently with the trans- formation of low pH monoclinic buserite to hexagonal H-rich birnessite (Drits et al. 1997; Silvester et al. 1997). The first mechanism is associated with the fast dispropor- tionation of layer Mn31 according to 2Mn → Mn 1 Mlayer 1 Mn , where M 31 41 layer of Mn31. The number and size of these domains increase with the extent of oxidation and the total Co concentration in the solution, and this accounts for the decreasing capacity of buserite to oxidize Co. The weight of structural evidence indicates that Co is oxidized by Mn31 rather than Mn41. Thermodynamic considerations indicate that under the solution pH conditions employed in this study Mn31 is the more likely electron sink for the oxidation of Co21. This study also shows that the high affinity of Co for man-